Detection of Porcine Adulteration in Cosmetic Cream Formulation via TaqMan Probe Real-Time Polymerase Chain Reaction - S S Abd-Gani; S Mustafa; M N Mohd Desa; N F Khairil Mokhtar; U K Hanapi; Z Zakaria; N Yahaya; W M A Wan Sulaiman (Science Publishing Corporation, 2024)
Volume: 7 No: 4